STUDY ON SHARPENING OF NARROW BAND SAW BLADES (Innovation in Woodworking Industry and Engineering design, 2026)
Sharpening and smoothing of cutting tools are basic and final stages in their preparation as well. Moreover, in these processes can not always get a edge with the necessary quality. This requires engineering and technical staff directly involved in the maintenance of the in-struments to have good depth knowledge and practical skills.The article presents results of experimental studies of narrow band saw blades sharpening with abrasive tools with ceramic and organic bond. The indicators of performance and quality of abrasive tools are defined. The durability of sharpened band saw blades was determined.